Elipse do SV e distribuição de advérbios em Português Língua de Herança e L2 - Santos, Ana Lúcia (2013)
This study compares the performance of adult L2 speakers of European Portuguese (EP) and 9-10 year-old heritage children acquiring EP concerning their knowledge of two aspects of grammar, adverb placement and VP ellipsis, which depend on knowledge of a core syntactic property of the language, verb movement. Regarding adverbs, the results do not show evidence of German V2 influence: both heritage children and L2 adults accept non V2 word orders. Performance in the VP ellipsis task is more complex: heritage children produce VP ellipsis at the level of controls, as opposed to L2 speakers; however, L2 and (possibly also) heritage speakers show some crosslinguistic influence effects.